Presynaptic Mechanisms and KCNQ Potassium Channels Modulate Opioid Depression of Respiratory Drive - Wei, Aguan D.; Ramirez, Jan-Marino (Frontiers in Physiology, 2019)
Opioid-induced respiratory depression (OIRD) is the major cause of death associated with opioid analgesics and drugs of abuse, but the underlying cellular and molecular mechanisms remain poorly understood. We investigated opioid action in vivo in unanesthetized mice and in in vitro medullary slices containing the preBötzinger Complex (preBötC), a locus critical for breathing and inspiratory rhythm generation. Although hypothesized as a primary mechanism, we found that mu-opioid receptor (MOR1)-mediated GIRK activation contributed only modestly to OIRD. Instead, mEPSC recordings from genetically identified Dbx1-derived interneurons, essential for rhythmogenesis, revealed a prevalent presynaptic mode of action for OIRD. Consistent with MOR1-mediated suppression of presynaptic release as a major component of OIRD, Cacna1a KO slices lacking P/Q-type Ca2+ channels enhanced OIRD. Furthermore, OIRD was mimicked and reversed by KCNQ potassium channel activators and blockers, respectively. In vivo whole-body plethysmography combined with systemic delivery of GIRK- and KCNQ-specific potassium channel drugs largely recapitulated these in vitro results, and revealed state-dependent modulation of OIRD. We propose that respiratory failure from OIRD results from a general reduction of synaptic efficacy, leading to a state-dependent collapse of rhythmic network activity.